(untitled) (Research, Society and Development, 2024)
Introduction: Orthoses, Prostheses and Special Materials (OPME) are medical devices used to correct deformities, structural support or replace parts of the human body. Objective: Verify the OPME management process used by the Hemodynamics Service, aiming to present potential interventions for its qualification. Methodology: This is a cross-sectional, quantitative, and retrospective action research (January to December 2021), using the Hemodynamics OPME form from the Fundação Hospital de Clínicas Gaspar Vianna (FHCGV) and the State’s Electronic Administrative Process of Pará. Results: Records were found of 18 prosthesis implantation procedures for occlusion of the Interatrial Communication, for both sexes, at a cost of R 524,995.00. There were 63 endovascular procedures in 2021. The average waiting time for patients is approximately 88.6 days. Conclusion: The OPME topic is complex, and little explored by scholars, however, it requires “many hands” to obtain the biggest objective, which is the quality provided to the user. It is believed that interventions to qualify the OPME management process at FHCGV will provide improvements in the management of the OPME sector, as well as the Institution’s processes and flows that will provide quality service to the user.